Psikologi Pada Masa Yunani Kuno Menurut Beberapa Tokoh - Damanik, Tegar Triwibowo; Harahap, Artika Hazrah; Batubara, Farhana (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2024)
This study aims to examine the early development of psychological thought during Ancient Greece by analyzing the contributions of several key figures who had a significant influence on the foundational ideas of psychology. Ancient Greece was a crucial period in the history of human thought, where concepts of the soul, mind, and human behavior began to be discussed philosophically and systematically. Using a qualitative approach through literature review, this research explores the thoughts of figures such as Socrates, Plato, Aristotle, and Hippocrates in understanding the nature of the human being and the soul (psyche). Socrates emphasized the importance of introspection and self-knowledge as the main foundation for attaining virtue and truth. Plato introduced the concept of dualism between soul and body, and divided the soul into three parts: rational, emotional, and appetitive. Meanwhile, Aristotle viewed the soul as the vital principle of life that is united with the body and developed an empirical approach to understanding mental functions. On the other hand, Hippocrates contributed from a medical perspective with the theory of four bodily humors, which were believed to influence personality and psychological conditions. The findings of this research indicate that although not scientific in the modern sense, the thoughts of Ancient Greek philosophers laid an important foundation for the development of psychology. Concepts such as soul, reason, emotion, and human behavior began to be studied systematically and inspired subsequent thinkers. By understanding this intellectual legacy, it can be appreciated that psychology has deep roots in ancient philosophy, which continues to contribute to the development of modern psychological theories.